2000
DOI: 10.1080/13032917.2000.9686990
|View full text |Cite
|
Sign up to set email alerts
|

Designing Self-Reply Questionnaires to Survey Tourists: Issues and Guidelines for Researchers

Abstract: The use of self-reply questionnaires as a data collection instrument is common intourism research. However, while there is a long tradition of use of these instruments in social science research, there has been little discussion of the particular needs and challenges created by tourism situations. This paper blends both theory, practical and experience to suggest a range of issues and guidelines which researchers may find useful in preparing a selfreply questionnaire. A number of technical issues associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hung & Petrick (2011) indicate that to better understand and manage South Africa's CMT assets, it is crucial to know the market that uses them, the reasons why people travel and what the visitors would like to gain from their trip. Similar sentiments are expressed by Orams & Page (2000) who indicate that examining visitor profiles (especially understanding tourists, who they are and what their attitudes, beliefs and desires are) is an important aspects of tourism research. Lucrezi et al's (2018) study of beachgoers in South Africa revealed that the profile and perceptions of beachgoers differed in relation to the level of urbanisation and geographic location of the beaches.…”
Section: Cmt Researchmentioning
confidence: 61%
“…Hung & Petrick (2011) indicate that to better understand and manage South Africa's CMT assets, it is crucial to know the market that uses them, the reasons why people travel and what the visitors would like to gain from their trip. Similar sentiments are expressed by Orams & Page (2000) who indicate that examining visitor profiles (especially understanding tourists, who they are and what their attitudes, beliefs and desires are) is an important aspects of tourism research. Lucrezi et al's (2018) study of beachgoers in South Africa revealed that the profile and perceptions of beachgoers differed in relation to the level of urbanisation and geographic location of the beaches.…”
Section: Cmt Researchmentioning
confidence: 61%
“…Eigen values equal to or above 1.0 were considered. The factor loading above 0.40 was used to explain the factor [61,62]; the percentage of variance that explained the results was at least 61.2% [63]. A reliable measure, the Cronbach's coefficient alpha, was calculated to examine the internal consistency of items with each dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Children under the age of 18 were not asked to complete the survey. Surveys were anonymous in an attempt to avoid problems of 'social desirability' whereby individuals select the response they believe is the 'correct' one [27].…”
Section: Survey Methodsmentioning
confidence: 99%